EFEKTIVITAS SERAPAN P DAN HASIL PADI (Oryza sativa L.) SAWAH AKIBAT PEMBERIAN PUPUK Si DAN ASAM HUMAT - Muhammad Dzikrullah; Wanti Mindari; Rossyda Priyadarshini (UPN VETERAN JAWA TIMUR, 2021)
The increasing population and the problem of land use change that continues to increase raises the problem of food security. Government programs have been carried out such as the expansion of marginal land in coastal areas, namely saline land. The research objective was to assess the effectiveness of P uptake due to the aplication of humic acid and silica on lowland rice crop production. The research method was arranged in a randomized block design that was repeated 3 times. Size of planting 2x2 m2, 4 kinds of treatment include; a. control b. humic acid c. silica d. humic acid + silica. The results showed that the application of humic acid + silica had a significant affect the rice growth with an average plant height of 85,74 cm at 10 mst and rice production of 4,20 ton.ha-1. Humic acid + silica can also improve soil chemical properties : pH 6,95 CEC 40,24 and P nutrient 197,6. This is because the ability of humic acid to chelate by removing the Pbonds from the uptake of metal and silica elements can increase the P content in the soil into a from that is more available to plants.